Access to institutional delivery care and reasons for home delivery in three districts of Tanzania - Exavery, Amon (BioMed Central, 2014)
INTRODUCTION: Globally, health facility delivery is encouraged as a single most important strategy in preventing maternal and neonatal morbidity and mortality. However, access to facility-based delivery care remains low in many less developed countries. This study assesses facilitators and barriers to institutional delivery in three districts of Tanzania. METHODS: Data come from a cross-sectional survey of random households on health behaviours and service utilization patterns among women and children aged less than 5 years. The survey was conducted in 2011 in Rufiji, Kilombero, and Ulanga districts of Tanzania, using a closed-ended questionnaire. This analysis focuses on 915 women of reproductive age who had given birth in the two years prior to the survey. Chi-square test was used to test for associations in the bivariate analysis and multivariate logistic regression was used to examine factors that influence institutional delivery. RESULTS: Overall, 74.5% of the 915 women delivered at health facilities in the two years prior to the survey. Multivariate analysis showed that the better the quality of antenatal care (ANC) the higher the odds of institutional delivery. Similarly, better socioeconomic status was associated with an increase in the odds of institutional delivery. Women of Sukuma ethnic background were less likely to deliver at health facilities than others. Presence of couple discussion on family planning matters was associated with higher odds of institutional delivery. CONCLUSION: Institutional delivery in Rufiji, Kilombero, and Ulanga district of Tanzania is relatively high and significantly dependent on the quality of ANC, better socioeconomic status as well as between-partner communication about family planning. Therefore, improving the quality of ANC, socioeconomic empowerment as well as promoting and supporting inter-spousal discussion on family planning matters is likely to enhance institutional delivery. Programs should also target women from the Sukuma ethnic group towards universal access to institutional delivery care in the study area.